2013
DOI: 10.3168/jds.2013-6741
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific pathogenicity of putative host-adapted and nonadapted strains of Streptococcus uberis in dairy cattle

Abstract: Streptococcus uberis is an important cause of intramammary infection in dairy cattle. Strains of Strep. uberis appear to differ in their ability to cause disease based on previous epidemiological studies. We explored the pathogenicity of 2 strains of Strep. uberis, where one strain represented a putatively host-adapted type based on its ability to cause persistent infection and to spread from cow to cow in a lactating herd. This type was part of a clonal complex that is commonly associated with bovine mastitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(140 citation statements)
references
References 41 publications
13
122
0
5
Order By: Relevance
“…The Hp course for the IMC closely trailed the dynamics of cytokines such as TNFα, IL-8 and IL-1β in the milk as demonstrated by Tassi et al (2013). The Hp and SAA concentrations had not reverted to basal levels by the end of the collection period at 312 h (Figure 1).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The Hp course for the IMC closely trailed the dynamics of cytokines such as TNFα, IL-8 and IL-1β in the milk as demonstrated by Tassi et al (2013). The Hp and SAA concentrations had not reverted to basal levels by the end of the collection period at 312 h (Figure 1).…”
Section: Resultsmentioning
confidence: 83%
“…Material and methods Intramammary challenge of six (6) udder quarters of six mid-lactation cows were carried out using a host-adapted S. uberis strain FSL Z1-048 (Tassi et al, 2013). All quarters were shown to be free of S. uberis infection by bacteriology prior to challenge.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been publications reporting the quantification of IL-17A protein in cattle using the anti-bovIL-17A ELISA Vetset marketed by Kingfisher Biotech [10, 11, 39, 41, 42]. A principal objective of our study was to use the transfected CHO cells and their expressed recombinant proteins as defined standards to identify cross-reactive antibodies and to further refine methods to detect bovIL-17A and ovIL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of IL-17 family members at the protein level in ruminant species has been limited by the paucity of species-specific reagents with the exception of one commercially-available ELISA kit to detect bovine IL-17A (Kingfisher Biotech). Using this ELISA, Flynn et al [10] have shown the capacity of Neospora caninum -infected bovine macrophages to stimulate IL-17A production in naive CD4+ve T cells while Tassi et al [11] have shown the presence of IL-17A in milk from lactating cattle infected by Streptococcus uberis .…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, a plasminogen activator factor and a CAMP factor have also been recorded [33]. In fact, Tassi et al [34] could show that S. uberis strains may also be differentiated into host-adapted, pathogenic strains, and non-adapted, basically apathogenic strains.…”
Section: Virulence Factorsmentioning
confidence: 99%